A micro trigeneration system with scroll-based organic Rankine cycle and membrane-based liquid desiccant cooling - Chen, Ziwei (2018)
The emergence of decentralized energy resources has brought numerous novel and advanced designs of efficient power generation systems with utilisation of renewable energy for locally provided, sustainable and cost-effective energy production. The micro trigeneration system has been a highly anticipated solution to fulfil domestic energy requirements, allowing simultaneous generation of electricity, heating and cooling from one primary source. As a matter of fact, the micro trigeneration system is still under research and development stage, with limited available demonstrations around the world. Current laboratory experimental and simulation studies mainly focus on integrations of mature technologies, whereas many promising alternatives have not been widely explored, for example organic Rankine cycle (ORC) and liquid desiccant cooling technology. The main aim of this thesis is to technically develop and evaluate a novel micro trigeneration system with a combination of scroll-based ORC and membrane-based liquid desiccant cooling (MLDC). In principle, the micro trigeneration system provides highly efficient energy conversion in a decentralized manner, as the scroll-based ORC has superior abilities in generating electricity and providing sufficient thermal output that matches the low-temperature regeneration requirement of the liquid desiccant in the MLDC. In terms of system sustainability, compact linear Fresnel reflectors (CLFR) can be one option of the primary energy source for the micro trigeneration system. A comprehensive literature review has demonstrated that no work has been conducted previously on such a system. In this thesis, the possibility of integrating CLFR to power generation systems has been firstly investigated and a detailed optical design of the CLFR-hybrid system has been conducted through geometrical modelling and experimental work. Results demonstrate that the CLFR-hybrid system with polar orientation is feasible to efficiently convert the absorbed solar energy into thermal energy, which thereby can be utilised for powering the micro trigeneration system. The concept of the novel micro trigeneration system with scroll-based ORC and MLDC has been critically examined and energy performance of the two main components, namely scroll-based ORC and MLDC have been evaluated respectively through both theoretical modelling and experimental work. Experimental tests show that the scroll-based ORC electric output of 564.5W, scroll expander isentropic and volumetric efficiencies of 78% and 83% are achievable at a 1kW capacity. In terms of MLDC, experimental results indicate the importance of system mass balance between the membrane-based dehumidifier and regenerator for continuous operation. Under the steady operating condition of MLDC, a supply air temperature of 20.4°C with dehumidification effectiveness of 0.3 and system COP of 0.70 are attainable at calcium chloride (CaCl2) solution concentration of 36%. Simulations based on a validated and comprehensive system model demonstrate the feasibility of pairing the scroll-based ORC and MLDC for the microre trigeneration system. The exhaust heat from the scroll-based ORC effectively fulfils the regeneration requirement of the MLDC. The inclusion of MLDC facilitates the micro trigeneration system overall efficiency with an increase of approximately 35.49%, compared to that of ORC-based separate power generation. Theoretical results show that the proposed micro trigeneration system has the overall system efficiencies of 38.96% in cogeneration mode and 41.23% in trigeneration mode. The thesis makes contribution to the knowledge of micro trigeneration technology, distributed power generation, energy conversion and air conditioning. Moreover, the presented parametric studies of CLFR, ORC and MLDC can be employed for designing and optimizing the relevant individual components. Regarding the future work, this thesis recommends more in-depth system modelling with a combination of CLFR, ORC and MLDC, logic optimisation of the micro trigeneration system and comprehensive field trial testing of the micro trigeneration system in building context.